2015
DOI: 10.1063/1.4930916
|View full text |Cite
|
Sign up to set email alerts
|

High pressure synthesis of amorphous TiO2 nanotubes

Abstract: Amorphous TiO2 nanotubes with diameters of 8-10 nm and length of several nanometers were synthesized by high pressure treatment of anatase TiO2 nanotubes. The structural phase transitions of anatase TiO2 nanotubes were investigated by using in-situ high-pressure synchrotron X-ray diffraction (XRD) method. The starting anatase structure is stable up to ∼20GPa, and transforms into a high-density amorphous (HDA) form at higher pressure. Pressure-modified high- to low-density transition was observed in the amorpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The enhancement of transition pressure could be affected by the length of the nanowires. Although the anatase irreversibly transforms to an amorphous or other crystalline phases, the morphological feature, such as nanotube, nanowire, and porous structure, can be well maintained. Second, the compressibility is also strongly affected by NP shape. Park et al compared the compressibility of rod-shaped anatase TiO 2 (3.5 nm × 21 nm, grow along [100]) and rice-shaped NPs (3.8 nm × 5 nm, grow along [001]) NPs (see Figure d) .…”
Section: Pressure Induced Np Atomic Structure Phase Transitionmentioning
confidence: 99%
“…The enhancement of transition pressure could be affected by the length of the nanowires. Although the anatase irreversibly transforms to an amorphous or other crystalline phases, the morphological feature, such as nanotube, nanowire, and porous structure, can be well maintained. Second, the compressibility is also strongly affected by NP shape. Park et al compared the compressibility of rod-shaped anatase TiO 2 (3.5 nm × 21 nm, grow along [100]) and rice-shaped NPs (3.8 nm × 5 nm, grow along [001]) NPs (see Figure d) .…”
Section: Pressure Induced Np Atomic Structure Phase Transitionmentioning
confidence: 99%
“…To eliminate, or at least reduce, the controversy concerning the compressibility and transformation mechanism, we study the high-pressure behavior of bulk ZnO polycrystalline. In addition, studies have shown that high pressure is an effective method for the synthesis of new materials and a powerful approach to regulating the morphology of materials through the metastabilization of the high-pressure treatment. Synthesis of ordered amorphous carbon clusters (OACC) with the incompressibility comparable to diamond is a typical example . In this study, the average grain size for the acquired ZnO after full decompression was confirmed to be ∼10 nm.…”
Section: Introductionmentioning
confidence: 58%
“…[ 15 ] Coupling between planar and nonplanar modes in a CNT resonator resulted in a whirling motion, which can be used as an amplitude limiting mechanism in self‐resonating NEMS oscillators. [ 475,476 ]…”
Section: Fundamental Concepts Of Nano/micromechanical Resonatorsmentioning
confidence: 99%